Swedish Freemasonry in the Caribbean: How St. Barthélemy turned into an Island of the IXth Province - Önnerfors, Andreas (Editorial de la Sede del Pacífico de la Universidad de Costa Rica, 2009)
This paper deals with the establishment of freemasonry on St. Barthélemy, its connections to the Swedish Grand Lodge, its membership structure and activities mainly between 1797 and 1807. There are plenty of documents which describe ritual work, organisation and ideology. These connections have hitherto never been analysed and the paper will for the first time present source material from the Archive of the Swedish Order of Freemasons on the lodge La Sudermanie in the capital of the island, Gustavia.